Algorithmic Morality and Local Value Anchors: How ABS–SBK Mediates Digital Populism in Indonesia’s Regional Politics - Lestari, Yayuk; Rinaldi; Okditazeini, Vannyora (Yayasan Ilomata, 2026)
This study explores the intersection between social media discourse in West Sumatra and formal governmental processes, focusing on the cultural idiom Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS–SBK). This Minangkabau moral framework is analyzed as a highly